The Impact of Mindfulness-Based Stress Reduction on Blood Pressure and Life Quality in Hypertensive Women - Erni Tri Indarti; Puji Astutik (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension remains one of the major health issues worldwide. More women than men suffer from hypertension. Hypertension is not only caused by physical factors and lifestyle but is also significantly influenced by psychological factors such as stress. Stress can increase blood pressure and affect a person's physical and psychological functions, leading to a decline in their quality of life. Mindfulness-Based Stress Reduction is one physical and psychological strategy that has been shown to be successful in treating hypertension individuals. Finding out how mindfulness-based stress reduction affected the blood pressure and quality of life of hypertensive women in Pustu Nglaban, Nglaban Village, Loceret Subdistrict, Nganjuk District, was the goal of this study. This study employed a pre-experimental design using a one-group pre-post test methodology. The sample consisted of 30 respondents selected through purposive sampling. Standard operating procedures (SOP) were used to execute mindfulness-based stress reduction, a Onemed blood pressure monitor was used to measure blood pressure, and the WHOQOL BREFF questionnaire was used to evaluate quality of life. The WHOQOL BREFF questionnaire has high validity and reliability for measuring quality of life in adolescents, adults and the elderly namely r=0.949 and cronbach’s alpha 0.835. A paired-t test was used to analyze the data. Blood pressure and quality of life in women with hypertension are impacted by mindfulness-based stress reduction, according to the data analysis results, which indicated p-values of 0.000 for systolic blood pressure, 0.000 for diastolic blood pressure, and 0.000 for quality of life. For women with hypertension, mindfulness-based stress reduction is believed to be an alternate self-management treatment.